(untitled) (Fiep Bulletin - online, 2013)
The venous ulcers (UVS) are chronic wounds that result from chronic venous insufficiency (CVI), affect people of different ages, mostly elderly. As a key aspect in addressing the bearer of UVS we should take a systematic assistance based on protocol, which covers the clinical evaluation, early diagnosis, treatment planning, implementation of the plan of care, development and reassessment of pipelines and treatment. The purpose of this review article is to characterize the scientific output, protocols on venous ulcers, in the databases of the Virtual Health Library (VHL), PubMed and ISI Web of Knowledge, on the type of presentation, research method, type of study, language, year of publication and category. We selected 34: 05 in LILACS; 12 in MEDLINE, 06 in PUBMED; 11 in ISI Web of Knowledge. Predominated the articles in the form of abstract (85.3%), quantitative method (79.4%), type a descriptive study (58.8%), English (85.3%) and in 2001 (14, 7%), it was emphasized the assessment (41.2%), implementation and testing of protocols (29.4%) and diagnosis of care (17.6%). The drafting of a protocol of assistance to individuals with UV requires the involvement of the entire team of health care in a multidisciplinary approach, with purpose to implement the actions of health professionals and systematic assistance to be provided, in addition to providing grants for implementation of care.